Adapted Nested Force-Gradient Integrators: The Schwinger Model Case (Communications in Computational Physics, 2018)
We study a novel class of numerical integrators, the adapted nested force-gradientschemes, used within the molecular dynamics step of the Hybrid Monte Carlo(HMC) algorithm. We test these methods in the Schwinger model on the lattice, a wellknown benchmark problem. We derive the analytical basis of nested force-gradienttype methods and demonstrate the advantage of the proposed approach, namely reducedcomputational costs compared with other numerical integration schemes inHMC.